Analysis of Production Planning and Raw Material Inventory Control Using the Just-in-Time Method - Adam, Mufan; Sudarman, Daman (Transpublika Publisher, 2025)
PT. Palma Indo Boga (Catering Service) is a company engaged in catering, particularly for important events or other occasions. PT. Palma Indo Boga (Catering Service) requires raw material supplies ordered from suppliers; however, it often faces production process issues due to insufficient raw material supplies with the desired quality, caused by uncertainty from suppliers, as well as fluctuating raw material prices due to seasons or other factors. The research aimed to identify how planning at PT. Palma Indo Boga is conducted using the just-in-time method and to understand how the control of raw material inventory at PT. Palma Indo Boga is managed using the Just in Time method. Based on the findings, it can be concluded that production planning at PT. Palma Indo Boga is carried out in writing so that the production department can more easily execute the production process if it is made in writing so that it can be seen directly, accurately, in detail, and according to schedule, then PT. Palma Indo Boga does not stock raw materials in large quantities, as this can lead to the accumulation of raw material inventory that may spoil the raw materials and increase storage costs. PT. Palma Indo Boga often experiences both excess and shortage of raw materials, so PT. Palma Indo Boga orders raw materials according to production needs. However, if there is an excess of raw materials, it can be used as reserve stock, and if there is a shortage of raw materials, the company will reorder.